2013
DOI: 10.1016/j.ymssp.2012.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of turbine blade natural frequencies from casing pressure and vibration measurements

Abstract: Non-contact measurement of gas turbine rotor blade vibration is a non-trivial task, with no method available which achieves this aim without some significant draw-backs. This paper presents a truly non-contact method to estimate rotor blade natural frequencies from casing vibration measurements at a single engine operating speed. An analytical model is derived to simulate the internal casing pressure in a turbine engine including the effects of blade vibration on this pressure signal. It is shown that the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…In order to demonstrate the reliability of the models described in this paper, a test rig was designed and manufactured in order to replicate a BTT application and generate BTT measurements using commercial A-ECS and P-ECS and therefore validate the models. Based on a brief review of the literature of the existing test rigs built for monitoring the structural health of a machine [34][35][36][37][38], a test rig was designed that was composed of a bladed disk with 12 blades surrounded by a cylindrical casing. The bladed disk is clamped to the end of a rotating shaft supported by two bearings.…”
Section: Design and Fabrication Of Test Rigmentioning
confidence: 99%
“…In order to demonstrate the reliability of the models described in this paper, a test rig was designed and manufactured in order to replicate a BTT application and generate BTT measurements using commercial A-ECS and P-ECS and therefore validate the models. Based on a brief review of the literature of the existing test rigs built for monitoring the structural health of a machine [34][35][36][37][38], a test rig was designed that was composed of a bladed disk with 12 blades surrounded by a cylindrical casing. The bladed disk is clamped to the end of a rotating shaft supported by two bearings.…”
Section: Design and Fabrication Of Test Rigmentioning
confidence: 99%
“…Blade tip timing [2][3][4] and casing pressure measurements [5] have been employed as non-contact techniques for blade vibration analysis. These techniques are more reliable than contact techniques in terms of life expectancy under the very hostile conditions of high temperatures and pressures under which turbine blades operate [2].…”
Section: Turbomachinery Vibration Measurementmentioning
confidence: 99%
“…Forbes and Randall determined that the turbine engine casing acts as a filter to the internal dynamic pressure, and so the frequencies contained in both signals are the same [1]. In a turbine engine fan, the casing internal pressure peak travels with the rotor blade tips.…”
Section: Introductionmentioning
confidence: 99%
“…Forbes and Randall showed that each harmonic of the rotor speed carrier frequency produces its own set of sidebands, as shown in Figure 1 [1]. To determine rotor blade vibratory frequency from the casing internal pressure response in the frequency domain, Forbes and Randall developed the following equation ,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation